Perimenstrual exacerbation of symptoms in borderline personality disorder: evidence from multilevel models and the Carolina Premenstrual Assessment Scoring System - Eisenlohr-Moul, Tory A.; Schmalenberger, Katja (Psychological medicine, 2018)
BackgroundIndividuals with a borderline personality disorder (BPD) suffer from a constellation of rapidly shifting emotional, interpersonal, and behavioral symptoms. The menstrual cycle may contribute to symptom instability among females with this disorder.MethodsFifteen healthy, unmedicated females with BPD and without dysmenorrhea reported daily symptoms across 35 days. Urine luteinizing hormone and salivary progesterone (P4) were used to confirm ovulation and cycle phase. Cyclical worsening of symptoms was evaluated using (1) phase contrasts in multilevel models and (2) the Carolina Premenstrual Assessment Scoring System (C-PASS), a protocol for evaluating clinically significant cycle effects on symptoms.ResultsMost symptoms demonstrated midluteal worsening, a perimenstrual peak, and resolution of symptoms in the follicular or ovulatory phase. Post-hoc correlations with person-centered progesterone revealed negative correlations with most symptoms. Depressive symptoms showed an unexpected delayed pattern in which baseline levels of symptoms were observed in the ovulatory and midluteal phases, and exacerbations were observed during both the perimenstrual and follicular phases. The majority of participants met C-PASS criteria for clinically significant (⩾30%) symptom exacerbation. All participants met the emotional instability criterion of BPD, and no participant met DSM-5 criteria for premenstrual dysphoric disorder (PMDD).ConclusionsFemales with BPD may be at elevated risk for perimenstrual worsening of emotional symptoms. Longitudinal studies with fine-grained hormonal measurement as well as hormonal experiments are needed to determine the pathophysiology of perimenstrual exacerbation in BPD.